Tracking daily steps: an investigation on a small post-secondary campus - Brent D. Bradford; Adam Howorko; Erinn Jacula; Jason Daniels; Shaelyn Hunt; Nicole Correia (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2020)
The production of mood-regulating chemicals (e.g. serotonin) may be impacted through prolonged or acute stress events. If a serotonin-deficit exists, depression-related illnesses may result, with such illnesses projected to become the second highest lifetime burden of disease. Critically, physical activity has been found to assist in increasing serotonin levels, positively impacting adult neurogenesis and mood. The purpose of this study was to track daily steps (physical activity) employing a step-counting technology across a small Canadian university. Guided by the research questions: Can tracking daily steps encourage elevated levels of physical activity? and What differences, if any, exist between physical activity levels amongst students and faculty/staff?, such an understanding may add to the current body of knowledge concerning physical activity levels in educational institutions. Over a 9-week period, students (n = 32) took significantly more steps than faculty/staff (n = 16), and significantly more in Week 9 than in Week 2.